MANAJEMEN INOVASI KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN (STUDI MULTI SITUS DI MTsS MAMBA'UL MA'ARIF MONTOR DAN MTsS ITTIHADUL WAQIFIN NAGASAREH): MENINGKATKAN MUTU PENDIDIKAN - Ziana Walidah; Ahmad Thohirin; A. Faizin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Curriculum Innovation Management, Education Quality The research in this thesis departs from the phenomenon that curriculum and learning innovation is intended as an idea, concept or action to solve problems related to the principle of relevance between learning materials and student needs, between the quality of learning in schools and graduate users in the workforce, and the fulfillment of community needs. So that matters related to improving cognitive, affective, and psychomotor quality are truly embedded in students and to build the popularity of madrasah competitiveness. This research focuses on curriculum innovation management in improving the quality of education in madrasah, for that in planning, implementation, and evaluation it is described into three research questions, namely: 1. How is curriculum innovation management in improving the quality of education at MTsS Ma'arif Montor and MTsS Ittihadul Waqifin Nagasareh? 2. What are the factors that influence curriculum innovation management in improving the quality of education at MTsS Mamba'ul Ma'arif Montor and MTsS Ittihadul Waqifin Nagasareh? 3. Curriculum management model Curriculum innovation in improving the quality of education at MTsS Mamba'ul Ma'arif Montor and MTsS Ittihadul Waqifin Nagasareh?. This study uses a descriptive method with a multi-case study design. The researcher acts as a human instrument.